Studi Literatur: Pengaruh Kepemimpinan Terhadap Kinerja Karyawan - Fajriani Putri Kholisoh; Elva Vhillia Aenina; Rysna Setia Yuliandri; Eman Sulaeman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Leadership has a significant and positive impact on employee performance. Employee behavior and performance can be influenced by good leadership; this can create a healthy work culture and ensure that everyone in the company is committed to achieving common goals. The purpose os this research is to understand, examine, and provide a deeper understanding of how leadership factors can influence employee performance. This Research employs a literature study approach using library research methods, which involves reanalyzing previous studies related to the influence of leadership on employee performance. Data is obtained from the literature of prior research, and study is classified as qualitative, producing descriptive data that can then be evaluated and interpreted narratively to provide insights.